Etiological and Pathogenic Factors in Congenital Diaphragmatic Hernia - Sluiter, I.; Veenma, D.; van Loenhout, R.; Rottier, R.; de Klein, A.; Keijzer, R.; Post, M.; Tibboel, D. (European Journal of Pediatric Surgery, 2012)
Congenital diaphragmatic hernia (CDH) is a congenital anomaly associated with an increased mortality and morbidity. In this article, we review the currently known etiological and pathogenic factors in CDH.
Keywords: congenital diaphragmatic hernia; ethics; pathogenic factors